2018
DOI: 10.1111/eci.12956
|View full text |Cite
|
Sign up to set email alerts
|

Predicting obstructive coronary artery disease using carotid ultrasound parameters: A nomogram from a large real‐world clinical data

Abstract: Total number of plaques, area of maximum soft, hard and mixed plaques showed significantly incremental prediction ability over CRF. A nomogram based on these factors provided an intuitive and practical method in detecting CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the present study, we found a higher carotid plaque count and more carotid stenotic branches, more severe Computational and Mathematical Methods in Medicine stenosis, and higher carotid AS in the CHD group. Numerous studies have recently shown a significant association between peripheral arterial plaque and CHD [18][19][20]. Polak et al [21] showed that in multivariate corrected analysis, all plaque parameters were significantly associated with CHD incidence, with hazard ratios ranging from 1.27 to 1.80, with the strongest association for IMT >1.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found a higher carotid plaque count and more carotid stenotic branches, more severe Computational and Mathematical Methods in Medicine stenosis, and higher carotid AS in the CHD group. Numerous studies have recently shown a significant association between peripheral arterial plaque and CHD [18][19][20]. Polak et al [21] showed that in multivariate corrected analysis, all plaque parameters were significantly associated with CHD incidence, with hazard ratios ranging from 1.27 to 1.80, with the strongest association for IMT >1.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been shown to be more accurate than conventional systems for predicting outcomes in cardiovascular diseases ( Wu et al, 2018 ). To explore the potential of MIF gene variation, we established a nomogram composed of MIF rs2070766 genotypes, diabetes, WBC, TC and HDL-C to predict the risk of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the outcome of late cardiac dysfunction, doctors have been exploring factors such as negative ventricular remodeling, left ventricular contraction, and diastolic dysfunction. Among these factors, the severity of coronary artery disease is related to ventricular remodeling and left ventricular function 3,4. In elderly patients with CHD, the left atrium causes constant progression of left ventricle and aorta remodeling and progressive decline of left ventricular systolic function.…”
Section: Discussionmentioning
confidence: 99%